(untitled) (Fiep Bulletin - online, 2015)
A method of lambaeróbica gained national proportion, due to expansion and public acceptance of Bahian music and the emergence of various groups, who spread the pace throughout Brazil. There was an increase in the demand mode for slimming purposes. This study aimed to analyze the reduction of body fat in practicing this sport and characterizes them by dermatoglyphic. Participants were 24 female subjects, the only practicing lambaeróbica, with participants from two weekly sessions lasting 60 minutes. By the end of the survey totaled up 35 sessions. For the assessment of body fat from skinfold protocol with generalized equation for body density (Petroski, 1999) was used. As for the density conversion relative to the fat, we used the Siri equation (1961). For the identification of dermatoglyphic characteristics, protocol by Cummins & Midlo (1961, apud Fernandes Filho and Ferreira, 2008) was used, allowing the division in two oxidative and glycolytic groups. Comparing the relative fat (%BF) pre participation (n = 23) showed a decrease of -0.8 (-2.9%) between the means (p = 0.70). Oxidative group (n = 8) compared the results of the pre-test results with 28.6 ± 6.4 27.8 ± post-test was decreased by -4.7 5.4 (-16%), although not confirming statistical significance (p <0.05) .The glycolytic group (n = 15) had lower results between the pre-process testing participation 27.7 ± 8.2% and after 27.7 ± 6.7% involvement , an increase of 0.02 (0.05%) of body fat (p = 1.0). This research was observed through the data need to increase the weekly sessions of the activity and also greater control variable intensity.